Analisa Produksi Bio-Etanol Dari Kulit Singkong Dengan Proses Thermal - Sabilah, Laode Muhamad Zakirus; Mangalla, Lukas Kano; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2020)
Cassava skin is a waste of high-carbohydrate cassava that can be treated asa an alternative fuel source. As for the purpose of this study, it is to know how to produce bioethanol from cassava skin and how much ethanol is produced in the fermentation destilation procwss. Bioethanol research from the cassava skin is made by means of a fermentation process using a 9 and 12 day fariation with a 20,4 and 60 gram supplement of a mixture (leaven/yeast) of a 20,4 and 60 gram that is cut off by sample destilting devices. Research shows that the longer the fermentation from a mixture of refined caskbark and yeasts does not significantly affect the ethanol produced, since ethanol results from each fariation is 10%. Key words: Cassava suede, fermentation, bioethanol, renewable energy